Volatile fatty acids production and counting of protozoa ruminate in bovine supplemented with fat - Balieiro-Neto, Geraldo; Melloti, Laércio (Brazilian Journal of Veterinary Research and Animal Science, 2007)
Effects of tallow (Tallow) supplementation on counting of protozoa rumen and production of volatile fatty acids were studied in a Latin Square (3 x 3) design, with six canulated heifers (480 kg body weight), to evaluate three diets, without or with 3 and 6% of tallow. Ruminal liquid collections were made at the twentieth first day of each experimental subperiod at 0, 1, 2, 3, 4, 6, and 8 hours after first meal. There was significant reduction of total protozoa in the rumen content and change in the fermentation with increase in the molar percentage of propionate and reduction in the molar percentage of butyrate at 6% of tallow.